Apoptosis induction and ERK/NF‐κB inactivation are associated with magnolol‐inhibited tumor progression in hepatocellular carcinoma in vivo - Tsai, Jai‐Jen; Chen, Jiann‐hwa; Chen, Cheng Hsien; Chung, Jing‐Gung; Hsu, Fei‐Ting (Environmental toxicology, 2020)
Although hepatitis B and/or hepatitis C virus were recognized as major risk factor for the development of hepatocellular carcinoma (HCC), certain occupational, environmental, and lifestyle factors also play key roles in HCC tumorigenesis. Moreover, in molecular signaling route, extracellular signal‐regulated kinase (ERK)/nuclear factor kappa‐light‐chain‐enhancer of activated B cells (NF‐κB) signaling was found to be overexpressed and linked to poor prognosis in HCC. Thus, to identify possible nature compound that can suppress ERK/NF‐κB may be benefit to HCC patient. Magnolol, a natural compound derived from herbal plant Magnolia officinalis, has been recognized as a liver protection and antitumor reagent. However, whether magnolol‐inhibited HCC progression correlates with disruption of ERK/NF‐κB signaling is remained unclear. In this studies, we performed SK‐Hep1/luc2 HCC bearing animal model to investigate the anticancer efficacy and mechanism of magnolol on tumor progression. Tumor size and tumor growth rate were dramatically suppressed after treatment of magnolol. In addition, expression of phospho‐ERK (p‐ERK), NF‐κB p65 (Ser536), and tumor progression‐associated proteins, such as matrix metallopeptidase 9 (MMP‐9), vascular endothelial growth factor (VEGF), X‐linked inhibitor of apoptosis protein (XIAP), and CyclinD1 were all significantly decreased by magnolol. Most important, major extrinsic and intrinsic apoptosis signaling factors, including active caspase‐8 and caspase‐9 were both enhanced by magnolol. This study indicated that apoptosis induction through extrinsic/intrinsic pathways and blockage of ERK/NF‐κB activation were associated with magnolol‐inhibited tumor progression in HCC in vivo.